Die ontwikkeling van die menslike bewussyn: Die postmoderne vraag na God - Ferreira, IgnatiusW. (HTS teologiese studies, 2009)
The development of the human consciousness: The postmodern quest for GodThis article critically reflects upon ‘emerging Christians’ – those who have departed from a premodern (theistic) and modernist (secular) view of reality, and have rather embraced postmodernity in response to the cognitive dissonance they experience due to a clash of epistemological paradigms. The article discusses psychological theories on the development of human consciousness, and describes seven levels or stages of such development, namely the archaic, magical, mythological, rational, pluralistic, holistic and transpersonal levels. The article focuses on Ken Wilber’s integral psychological theory, better known as AQAL (All Quadrants, All Levels and All Lines), which also covers the internal and external dimensions of human consciousness, including an integral view on the so-called ‘states of human consciousness’. In doing so, the article aims to contribute to that aspect of pastoral care that focuses on psychological theory.